2020
DOI: 10.1002/nav.21936
|View full text |Cite
|
Sign up to set email alerts
|

Two‐agent scheduling with linear resource‐dependent processing times

Abstract: This paper considers a two‐agent scheduling problem with linear resource‐dependent processing times, in which each agent has a set of jobs that compete with that of the other agent for the use of a common processing machine, and each agent aims to minimize the weighted number of its tardy jobs. To meet the due date requirements of the jobs of the two agents, additional amounts of a common resource, which may be in discrete or continuous quantities, can be allocated to the processing of the jobs to compress the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…To improve the competition rate, the producer can allocate a certain amount of resources to each job to reduce the processing time. The multi-agent scheduling problem with resource allocation has been studied by Wang et al [17] for a two-agent scheduling with linear resource, for which a FPTAS is proposed for the NP-hard problem. Luo [18] studied the slack due date problem with convex resource, and presented an optimal solution algorithm with time complexity of O(N 3 ) for the two-agent minmax earliness, tardiness, and common decision variable, where N is the maximum number of jobs between the two agents.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the competition rate, the producer can allocate a certain amount of resources to each job to reduce the processing time. The multi-agent scheduling problem with resource allocation has been studied by Wang et al [17] for a two-agent scheduling with linear resource, for which a FPTAS is proposed for the NP-hard problem. Luo [18] studied the slack due date problem with convex resource, and presented an optimal solution algorithm with time complexity of O(N 3 ) for the two-agent minmax earliness, tardiness, and common decision variable, where N is the maximum number of jobs between the two agents.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, a large number of studies on scheduling problems in manufacturing and service systems have been conducted. These problems can be classified as single-machine scheduling [13,14] , parallel-machine scheduling [15,16] , flow-shop scheduling [17][18][19] , job-shop scheduling [20,21] , and their variants [22,23] . In recent years, researchers have proposed a new scheduling method, i.e., distributed scheduling, which aims at scheduling distributed manufacturing systems [24] .…”
Section: Introductionmentioning
confidence: 99%
“…Under CONW, SLKW, and DIFW assignments, we showed that these problems can be solved in polynomial time. Further extensions are addressing the above problems in the setting of flow shop and identical (unrelated) parallel machines, considering scheduling with resource-dependent processing times (Wang et al [26], and Wang et al [27]), or studying multitasking scheduling (Xiong et al [30]).…”
mentioning
confidence: 99%